Voices from the community: Developing effective community programs to support pregnant and early parenting women who use alcohol and other substances - Nathoo, Tasnim; Poole, Nancy; Bryans, Margaret; Dechief, Lynda; Hardeman, Samantha; Marcellus, Lenora; Poag, Elizabeth; Taylor, Marliss (First Peoples Child & Family Review, 2013)
Since the 1990s, many communities in Canada have worked to develop specialized programs to meet the needs of pregnant and early parenting women who use alcohol and other substances. These programs provide a range of services under one roof (a “single-access” or “one-stop shop” model), address women’s needs from a holistic perspective, provide practical and emotional support, and strive to reduce barriers to accessing care and support. Over the years, these programs have trialed new approaches to working with indigenous and non-indigenous women, their families, and their communities. In this paper, we describe the development of single-access programs in four different communities in Canada, discuss some of the elements of what makes these programs successful, and share our "lessons learned" over the years. We use examples from four different programs, including the Maxxine Wright Place Project in Surrey, BC; the Healthy, Empowered, Resilient (H.E.R) Pregnancy Program in Edmonton, AB; HerWay Home in Victoria, BC; and Manito Ikwe Kagiikwe in Winnipeg, MB. All four programs are based upon the "best practices" elements of: (1) engagement and outreach, (2) harm reduction, (3) cultural safety (4) supporting mother and child, and (5) partnerships. In addition to serving First Nations, Métis, Inuit and other indigenous women and their families, these programs have drawn upon indigenous knowledge in their program design, values, and philosophy and have collaborated with indigenous women in evaluation and research to track the successes of these programs and to improve service delivery.